Experimental Study on Tribological Characteristics of AA 6061 Alloy Reinforced with Al2O3 and B4C Particles (Journal of Engineering, 2018)
Two different composite materials were prepared by stir casting method of AA 6061 alloy as a matrix reinforced with two addition different ceramic materials Al2O3 and B4C of grain size   20 µm by 2.5, 5, 7.5 and10% in weight. The composite material with aluminum alloy as a matrix possesses a unique mechanical properties such as: high specific strength and hardness, low density, and high resistance to corrosion and friction wear. This composite is widely used in automotive parts space and marine applications.Pin-on-disc technique was used to calculate the wear rate for each addition of Al2O3 and B4C particles. Rockwell hardness test and optical micrographs examinations were carried out to analyze, compare, and evaluate the addition of reinforced particles. The results of this investigation appeared that the 7.5% of ceramic particles addition give highest values of the hardness and wear resistance.